2018
DOI: 10.1038/nature25168
|View full text |Cite
|
Sign up to set email alerts
|

Clonal analysis of lineage fate in native haematopoiesis

Abstract: SUMMARY Hematopoiesis, the process of mature blood and immune cell production, is functionally organized as a hierarchy, with self-renewing hematopoietic stem cells (HSCs) and multipotent progenitor (MPP) cells sitting at the very top1,2. Multiple models have been proposed as to what the earliest lineage choices are in these primitive hematopoietic compartments, the cellular intermediates, and the resulting lineage trees that emerge from them3–10. Given that the bulk of studies addressing lineage outcomes have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
454
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(531 citation statements)
references
References 41 publications
57
454
1
1
Order By: Relevance
“…The HPC2 population was not investigated in previous reports, 16,17,20 and labeling of platelets by HSCs were not traced in the studies by Sun et al and Busch et al Recently, it was reported that the megakaryocyte lineage is the predominant fate of HSCs in the native state. 33 Interestingly, HSCs have been shown to produce HPC2/MPP2 after brief in vitro culture without appreciable production of MPPs (termed ST-HSCs in Pietras et al 30 ). Therefore, it is tempting to speculate that the hierarchical order of hematopoiesis is different during native hematopoiesis than after transplantation, but further work is needed to decipher the hierarchical organization of hematopoiesis in the native state.…”
Section: Discussionmentioning
confidence: 99%
“…The HPC2 population was not investigated in previous reports, 16,17,20 and labeling of platelets by HSCs were not traced in the studies by Sun et al and Busch et al Recently, it was reported that the megakaryocyte lineage is the predominant fate of HSCs in the native state. 33 Interestingly, HSCs have been shown to produce HPC2/MPP2 after brief in vitro culture without appreciable production of MPPs (termed ST-HSCs in Pietras et al 30 ). Therefore, it is tempting to speculate that the hierarchical order of hematopoiesis is different during native hematopoiesis than after transplantation, but further work is needed to decipher the hierarchical organization of hematopoiesis in the native state.…”
Section: Discussionmentioning
confidence: 99%
“…[37] In a subsequent study, this strategy revealed that half of the Mk lineage appeared to be produced independently from other lineages by the HSC compartment. [38] However, the authors suggested that the MEP stage could be too transient to be detected by their approach. [38]…”
Section: Alternatives To the Megakaryocytic-erythroid Progenitor (Mepmentioning
confidence: 99%
“…[38] However, the authors suggested that the MEP stage could be too transient to be detected by their approach. [38]…”
Section: Alternatives To the Megakaryocytic-erythroid Progenitor (Mepmentioning
confidence: 99%
“…Fluorescence-activated cell sorting (or FACS) greatly facilitated the purification of transplantable HSCs through positive and negative selection, as described in pioneering publications (e.g., [8] from Dr. Irving Weissman’s group). HSCs are widely believed essential to hematopoiesis under recovery or other stress conditions [913], and HSC transplantation has, therefore, been a key therapeutic strategy in combatting hematological disorders [14, 15]. Intriguingly, recent advances utilizing single-cell approaches have revealed at the apex of hematopoiesis a rare population of HSCs that can sustain all the hematopoietic lineages throughout the lifetime of the individual, and may be critical to the rapid hematopoietic response required by acute conditions.…”
Section: Introductionmentioning
confidence: 99%